A new alkylbenzoquinone from Embelia rowlandii Gilg. (Myrsinaceae). Issue 13 (3rd July 2019) - Bouzeko, Inest Larissa Tchomtchoua; Ndontsa, Blanche Laure; Mba Nguekeu, Yves Martial; Awouafack, Maurice Ducret; Wong, Chin Piow; Simo Mpetga, James Deke; Mbouangouere, Roukayatou; Tane, Pierre; Morita, Hiroyuki
Abstract: A new alkylbenzoquinone named embeliquinone (1 ) together with five known compounds, lupeol (2 ), 3- O -[6′- O -palmitoyl- β -d -glucosyl]-spinasta-7, 22(23)-diene (3 ), quercetin (4 ), (2 S, 3 S, 4 R, 8 E )-2-[(2′ R )-2′-hydroxy-heneicosanoylamino]-heneicosane-1, 3, 4-triol-8-ene (5 ), and β -sitosterol-3- O - β -d -glucopyranoside (6 ) were isolated from the MeOH leaf extract of Embelia rowlandii by using repeated open column chromatography techniques. The structure of the new compound was characterized by analyses of 1D- and 2D-NMR, and MS data. Embeliquinone (1 ) had moderate anti-cell proliferation activity against A549 cell line with the IC50 value of 21.8 μM. In addition, 1 exhibited weak antibacterial activities against Klebsiella pneumoniae and Staphylococcus aureus with an MIC value of 206.0 μM in both cases. Abstract :